Factors Influencing Investors to Invest in the Sharia Capital Market - Rina Nur Shabrina; Rifki Ismal; Achmad Firdaus (Tazkia Islamic Finance and Business Review, 2024)
This study aims to analyze the factors influencing individual investors' decision-making in the Indonesian Islamic Stock Exchange (BEI). The observed factors include Islamic financial literacy, Islamic investment literacy, and Islamic behavioral investment. This research employs descriptive analysis and causality testing using Structural Equation Modeling (SEM). A sample of 500 active retail investors in the Indonesian Islamic Capital Market was collected via Google Forms, and the data were analyzed using Confirmatory Factor Analysis (CFA). Hypotheses were tested through composite reliability analysis. The findings reveal that Islamic financial literacy, investment literacy, and behavioral investment have a positive and significant influence on investment decisions, with a determination coefficient of 0.79. However, the study also found that religious factors did not significantly affect investors' decision-making behavior. Keywords: Islamic Financial Literacy, Islamic Investment Literacy, Islamic Behavioral Investment, Investment Decision